Simulation and Control of Door Lock System Using PID Controller - Md Zain, Badrul Aisham (Journal of Advanced Mechanical Engineering Applications, 2021)
A proportional–integral–derivative (PID) controller (or three-term controller) is a feedback-based control loop mechanism that is extensively employed in industrial control systems and a range of other applications that need constantly modulated control. Technologies using PID controller can be considered efficient and secure compared to other control loop mechanism. The aim of this project is to produce a more efficient way of locking and unlocking the door instead of using traditional key method. Next, to produce a mathematical modelling of the PID controller system and use MATLAB software to validate the data. Lastly, to create a stable control system by introducing PID into the system and operate in a best manner. The analysis of stabilization of the system involving the time response analysis, root locus, bode plot and Nyquist plot via MatLab software. The usage of PID controller also involve on tuning the controller through try and error tuning has result to an overshoot percentage value of 8.3% comparing to the result without controller at 25%. To conclude, the present of PID controller into the system has set a major effect on the efficiency and keep the actual output from the door locking process as close to the target or setpoint output as possible.